The views of healthcare providers on providing a brief treatment to address methamphetamine use among patients with a dual diagnosis - Dannatt, Lisa (Department of Psychiatry and Mental Health, 2020)
BACKGROUND: Methamphetamine (MA) use disorder in individuals with severe mental disorders (SMDs) has significant impact on clinical presentation and care. Although treatments exist, these are met by significant challenges. Notably, brief treatments for MA use within the general population have been feasible, acceptable and effective. An individualized, integrated treatment for MA use within a psychiatric inpatient setting would allow adjustment of the treatment according to individual patient needs. It is important to understand the patient needs and potential service barriers to care before formulating a treatment. This study begins to address this gap by seeking to understand the views of healthcare providers on a brief treatment to address MA use among patients with a dual diagnosis. METHODS: Thirteen key stakeholders working with patients with mental disorders including severe mental disorders and co morbid MA use were interviewed using an open-ended semi- structured interview schedule designed to explore their views on a brief treatment for MA use among patients with a dual diagnosis. Interviews were transcribed and the framework approach was used to conduct data analysis. RESULTS: Numerous themes emerged from the data. First, there are multiple risk factors for MA use. Second, this use has a significant impact on multiple aspects of patient presentation and care including individual impacts, family impacts, and impact on care. Third, although treatments for MA use disorders exist, these have significant challenges at multiple levels. Lastly, the integration of a modified brief treatment for MA use in patients with dual diagnosis would be possible if it was adjusted to patient-specific needs within the existing system and if the team adapting the treatment were cognizant of existing and potential challenges. CONCLUSIONS: The adaptation and integration of a brief treatment for MA use among patients with severe mental disorders was considered possible and even necessary if existing and potential challenges were carefully addressed.